Increasing socio-emotional competence of childern through boy-boyan traditional games with the experiental learning method - Rahayu, Esti Widya; Iswinarti, Iswinarti; Fasikhah, Siti Suminarti (Indigenous, 2021)
Socio-emotional competence is important in children's development, because it can help them in problem solving, increase in prosocial behavior, form good relationships, and adapt to growing and complex demands. Lack of socio-emotional competence in the early stages of development is associated with aggressive tendencies, bullying, low problem solving, social isolation, rejection of relationship with peer, lack of skill in taking responsibility, involvement with crime, and drug use. Therefore, in increasing the set of competencies that children need for the future, boy-boyan become an alternative learning media through experience. With feedback from the games, children will get new knowledge to be applied in everyday life. A total of 60 male and female subjects aged 9-12 years were divided into three research groups, namely the experimental group 1 who received the boy-boy game method with experiential learning, the experimental group 2 who played only boy-boyan, and the control group. Method used is a quasi-experimental with a pretest-posttest subject design. Data analysis used Kruskal Wallis and Mann-Whitney, and the scale used was the Socio Emotional Competence Questionaire which was measured at the pretest and posttest. The results showed that there were significant differences between the three groups (ρ 0.000), and there was an increase in three aspects of socio-emotional competence in children through boy-boyan with the experiential learning method compared to only playing boy-boyan. Keywords: Childern ; Socio-Emotional Competence ; Traditional Play